Margaret Murray's Meat Curry. Issue 1 (10th June 2014) - Thornton, Amara
In 1937 in Jerash, Transjordan, Margaret Murray gave Gerald Lankester Harding recipes for meat curry and dahl. This article briefly traces each archaeologist's personal and professional trajectory as they moved between Britain and various imperial outposts, and situates the recipes within the complex contexts of their histories. The recipes, staples of Anglo-Indian cuisine, take on new meaning as symbols of the hybridity of archaeological identity in the late 19 th and early 20 th centuries.